A comparative trial of ice application versus EMLA cream in alleviation of pain during botulinum toxin injections for palmar hyperhidrosis - Alsantali A (Dove Medical Press, 2018)
Adel Alsantali Department of Dermatology, King Fahd Armed Forces Hospital, Jeddah, Saudi Arabia Background: Botulinum toxin is a safe and effective therapy for palmar hyperhidrosis, but the associated pain from injections limits the usefulness of this method of treatment. Purpose: To evaluate the efficacy of Eutectic Mixture of Local Anesthetics (EMLA) cream versus ice application in alleviation of pain during botulinum toxin injections for palmar hyperhidrosis. Methods: In this prospective study, 23 patients underwent palm Botox injections to treat their excessive sweating. In each patient, EMLA cream was applied to one palm and ice was applied directly before the injections in the other palm. Pain was evaluated using a Visual Analog Scale. Results: Statistically, there was a significant difference in pain control between EMLA cream group and ice application group (p<0.05). The average pain score on the hands where EMLA cream was applied was 8.9 (SD=0.81), whereas it was 4.8 (±0.9) in the ice group. Conclusion: In this study, the successful use of ice application in reducing pain by 40% in comparison to EMLA cream during Botox toxin injection for palmar hyperhidrosis is demonstrated.Keywords: ice, local anesthetics, EMLA, palmar hyperhidrosis, Botox injection, pain reduction